An amphora from the circle of the Hector Painter found in Hierapytna, Crete (LANX. Journal of the Scuola di Specializzazione in Beni Archeologici - Università degli Studi di Milano, 2020)
Among the incidental findings of Attic vases in the eastern area of Crete, is included a red-figure neck amphora. Until now, very little information was published about the vase, that was initially found in a burial in Ierapetra, the ancient Hierapytna. As the vase was never studied extensively, the purpose of this article is to provide an in-depth analysis of it, both from the point of view of production, and from an iconographical and iconological perspective. The shape of the vase will be discussed; furthermore, focus will be placed on its attribution to a hand close to the Hector Painter, and the contextual analysis of its graphic representations. To conclude, the article aims to highlight the importance of this discovery in the Cretan historical context of the third quarter of the 5th century BC, when Attic imports were scarce, following the long period of shortage of trade affecting the island throughout the Classical era.